Pengaruh Pembelajaran Inkuiri Terbimbing Melalui Pendekatan Saintifik di TK Negeri Pembina Bungi - Ima Ismail (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to: 1) to determine the description of the science abilities of children in group B before treatment with the guided inquiry method at Pembina Bungi State Kindergarten, 2) To determine the description of the development of science abilities of children in group B using the guided inquiry method at Pembina Bungi State Kindergarten. The research technique is an experiment with the design of this study One Groups Pretest-Posttest Design. Data collection techniques used in the study are observation, testing and documentation. The subjects of this study were 10 children divided by the study conducted pretest and posttest. The results of this study indicate that 1) the science abilities of children in group B1 with the guided inquiry method have the highest achievement of developing very well at 79% and the lowest value of 58%, and the average value is 71.3%. 2) the results of the posttest of the science abilities of children in group B1, the highest achievement developed very well at 92%, the lowest achievement developed according to expectations at 71%, and the average was 84.6%. This shows the influence of students' science abilities when given the guided inquiry method in group B at Pembina Bungi State Kindergarten, Baubau City. Overall, the study concludes that the guided inquiry method is effective in improving early childhood science learning outcomes, particularly in enhancing curiosity, critical thinking, and problem-solving skills in the classroom context.